(untitled) (Semiárida, 2020)
The objectives of the present study were: 1) to measure the chop length produced by different forage harvesters on maize, and 2) to evaluate the effect of chopping on voluntary dry matter intake and performance. The experiment was carried out with lactating cows and dry ewes during 20 days, being the first 6 days for adaptation of the experimental animals to the dieto The whole plant of maize CV. colorado La Holandesa was used as animal feed, cut by four different ways, the four treatments: 1) PE: cutting of the whole plant by sickle; 2) PS: cutting and chopping by a hammermill machine; 3) PO: cutting and chopping by a hammermill, transporter and fan, and 4) PF: cutting and chopping by a two ways mili with knives. The feed was offered ad libitum to 16 Holstein- Freisian lactating cows and to 16 dry, non-pregnant Corriedale ewes into two experiment within a randomized blocks design each. The three chopping machines produced particles of different chop length: PS: tassel: 91.3 mm ± 7.63; leaf: 100.3 mm ± 10.47; stem: 114.8 mm ± 7.05; PO: tassel: 60.1 mm ± 9.86; leaf: 58.0 ± 4.74; stem: 90.8 ± 9.10; PF: tassel: 13.0 mm ± 1.21; leaf: 45.3 mm ± 3,62; stem: 23.8 mm ± 2.17. Within each plant part, all comparisons among chop length produced by the three machines were highly significant (P<0.01). The voluntary intake of the lactating cows was not different between treatments (P> 0.05). The lowest value was obtained in PS (80.3 g/kg LWO.75) and the highest in PF (91,2 g) (PE: 88.1 g; PO: 85.2 g). The voluntary intake of ewes was significantly lower in PE (21.6 g/kg LWO.75) than in PS (36.2 g) and in PO (36.0 g). AII other comparisons between treatments were not significant (P>0.05). The particle size did not significantly affect mil k production of the lactating cows (PE: 13.02 liters/cow.day; PS: 10.24 liters; PO: 10.24 liters; PF: 11.78 liters) and liweweight loss of ewes (PE: 217 g/day; PS: 51 g/day; PO: 35 g/day; PF: 133 g/day). The results show that, under these experimental conditions, chop length of forage does not affect voluntary intake and performance of lactating cows or dry ewes; the voluntary intake of maize by the dry ewes, however, was very low, especially when the whole plant was offered as feed.